(untitled) (Journal of the Bangladesh Chemical Society, 2013)
Acrylamide (AAm)/carboxymethyl cellulose (CMC) blend hydrogels have been prepared by the application of gamma radiation from C0-60 source at room temperature (27°C). The preparation conditions such as effect of CMC concentration and radiation dose on gel fraction and swelling behaviors were investigated. The maximum value of gel fraction is obtained at 25 kGy radiation dose. The swelling properties were investigated in distilled water, saline solution (NaCl) and buffer medium. The maximum swelling value of hydrogel was obtained at 48 hours in water. The swelling ratio of hydrogel decreased with increase in concentration of NaCl in swelling medium. In buffer, it was found that swelling ratio increased with increase in pH of medium. Journal of Bangladesh Chemical Society, Vol. 25(2), 132-138, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15065